ON THE PHILOSOPHICAL CHARACTERISTICS OF THE CONCEPT OF “FUTUROLOGY” (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
In this article, the authors comprehensively examine the history of the developmentand transformation of futurology as a scientific discipline. The purpose of the study is to revealand briefly characterize the key ideas, concepts and events of the main stages of the developmentof futurology. Futurology in general is a generalized name for a set of concepts about the futureof the planet, humanity, processes and phenomena based on scientific knowledge and forecasts. Itis often understood as “the history of the future” or, as O. Fletheim proposed, “the philosophy ofthe future”, which will be an alternative to ideologies. Futurology is a multifaceted and interdisciplinary field of study, and there are many different theoretical approaches within it. It remainsan important tool for analyzing and understanding the future and for developing strategies for asustainable and positive future.
Keywords: Futurology, history of futurology, stages of futurology development, futurology as a branch of philosophy, theory, concepts.